SAT0456 The incidence of cardiovascular events in italian patients with systemic lupus erythematosus is lower than in north european and american cohorts: implication of disease–associated and traditional risk factors as emerged by a 16-year retrospective girrcs study. (12th June 2018) - Fasano, S.; Margiotta, D.P.; Gualtierotti, R.; Corrado, A.; Berardicurti, O.; Iacono, D.; Pierro, L.; Riccardi, A.; Giacomelli, R.; Cantatore, F.P.; Meroni, P.; Afeltra, A.; et al.
Abstract : Background: Cardiovascular (CV) disease is the leading cause of premature death among Systemic Lupus Erythematosus (SLE) patients1. Several studies have analysed the incidence of CV events in SLE patients. However, the majority of them have been conducted in American and North European countries 2–7. At the best of our knowledge, no studies in Italy have considered cumulative incidence and incidence rate of CV events in Italy. Objectives: The present study is devoted to estimate the incidence of a first ever CV event in Italian lupus patients from five rheumatologic tertiary units from North, Centre and South Italy and to search for features associated with and potentially causative of the detected differences. Methods: Clinical charts of SLE patients consecutively admitted to five Italian rheumatologic centres from November 1 st 2000 and December 31 st 2016 were retrospectively studied. Patients selected were free of CV events at baseline. CV cumulative incidence was evaluated as the proportion of patients who experienced a new CV event over the follow up period. CV incidence rate was expressed as the number of events in the cohort divided by the total number of years at risk. Our incidence was compared with that detected in the Italian general population and those reported in SLE cohorts from other countries. Results: The median duration of follow-up was 6 years (IQR=3–11). During the observational period, 39(cumulative incidence=7.6%) of the 511 patients had a first CV event with an incidence rate of 10.4/1000 person-years i.e. 12 times higher than in the general population. The CV cumulative incidence detected in our Italian cohort was similar to that reported in the Spanish cohort, but lower than those from North European and American cohorts. The Italian cohort differed from other SLE cohorts in some traditional risk factors (smoke, hypertension, dyslipidemia) and treatment with aspirin and hydroxychloroquine.(table1) Conclusions: Our study confirmed the increased CV risk in SLE compared with the general population. However, the incidence of CV events in our SLE series was lower than that detected in North European and American lupus cohorts. These disparities could be ascribed to the differences in the prevalences of traditional CV risk factors among the distinct cohorts. Nevertheless, our CV cumulative incidence was very similar to that detected in the Spanish cohort, despite their higher frequency of traditional risk factors. For this evidence, the geographic (Mediterranean) origin deserve to be considered. On the other hand, the slight difference detected between our series and Baltimore cohort2(where patients were examined every 3 months) underlines the need of a strict follow-up of the SLE patient. References: [1] Cervera R, et al. Medicine (Baltimore)2003. [2] Magder LS, Petri M. Am J Epidemiol2012. [3] Bertoli AM, et al. Lupus2009. [4] Bartels CM, et al. J Rheumatol2014. [5] Gustafsson J, et al. Arthritis Res Ther2009. [6] Hermansen M-L, et al. Rheumatol Oxf Engl2017. [7] Fernández-Nebro A, et al. Medicine (Baltimore)2015. Disclosure of Interest: None declared